2012
DOI: 10.1124/dmd.111.042416
|View full text |Cite
|
Sign up to set email alerts
|

Effects of theCYP2B6*6Allele on Catalytic Properties and Inhibition of CYP2B6 In Vitro: Implication for the Mechanism of Reduced Efavirenz Metabolism and Other CYP2B6 Substrates In Vivo

Abstract: ABSTRACT:The mechanism by which CYP2B6*6 allele alters drug metabolism in vitro and in vivo is not fully understood. To test the hypothesis that altered substrate binding and/or catalytic properties contribute to its functional consequences, efavirenz 8-hydroxylation and bupropion 4-hydroxylation were determined in CYP2B6.1 and CYP2B6.6 proteins expressed without and with cytochrome b5 (Cyt b5) and in human liver microsomes (HLMs) obtained from liver tissues genotyped for the CYP2B6*6 allele. The susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
65
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 36 publications
(71 reference statements)
7
65
0
Order By: Relevance
“…Nonetheless, this did not explain the differences between variants in methadone metabolism. Such varying ratios were also seen previously, with CYP2B6 systems using a single virus for the three proteins (P450, reductase, and b 5 ) (Xu et al, 2012;Gadel et al, 2013). When reductase levels are sufficient for catalytic activity, overexpression of reductase may not be a factor (Nakajima et al, 2002).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Nonetheless, this did not explain the differences between variants in methadone metabolism. Such varying ratios were also seen previously, with CYP2B6 systems using a single virus for the three proteins (P450, reductase, and b 5 ) (Xu et al, 2012;Gadel et al, 2013). When reductase levels are sufficient for catalytic activity, overexpression of reductase may not be a factor (Nakajima et al, 2002).…”
Section: Discussionsupporting
confidence: 68%
“…In addition to differences noted above between various expression systems, most have also not included cytochrome b 5 , and the absence or presence of b 5 may influence results. Efavirenz metabolism by both CYP2B6.1 and CYP2B6.6 was unchanged by b 5 , whereas bupropion metabolism by CYP2B6.1 was unchanged by b 5 but metabolism by CYP2B6.6 was diminished (Xu et al, 2012). The present results showed that b 5 increased methadone Cl int by CYP2B6.1 and CYP2B6.4 but not metabolism at therapeutic concentrations.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…We showed that variants in the CYP2B6 gene lead to reduced EFV metabolism (9,(30)(31)(32)(33). Several studies in HIV-1-infected individuals have demonstrated a strong association between these variants and EFV metabolism (reviewed in references 10 and 34).…”
mentioning
confidence: 86%